Analysis of Jinayah Fiqh on Actions Criminal Fraud Through Hypnosis Pinrang District - Rahmat Nurul Yakin; Mahsyar Mahsyar; Rahmawati Rahmawati (Program Studi Hukum Pidana Islam IAIN Parepare, 2022)
Fiqhi Jinayah's Analysis of the Crime of Fraud Through Hypnosis in Pinrang Regency, (supervised by Mr. H. Mahsyar, and Mrs. Rahmawati). This study aims to determine the modus operandi of the crime of fraud through hypnosis in Pinrang Regency, to determine the police's efforts in tackling the crime of fraud through hypnosis at the Pinrang Police, and to find out the views of Fiqhi Jinayah regarding the crime of fraud through hypnosis. This type of research is a qualitative research with a normative juridical approach. The data in this study were obtained from primary data, namely the police at the Pinrang Police and secondary data from the library and the internet. With interview data collection techniques and documentation. The results of this study indicate that 1. the mode used by fraud perpetrators through hypnosis is to trick the victim until the victim is unconscious and surrender all property owned or under at the time the crime took place. 2. In terms of tackling criminal acts of fraud through hypnotic operandi, the Pinrang Police have carried out preventive efforts, namely conducting patrols around the Pinrang district, especially areas where hypnotic fraud has occurred before and made announcements to the public to remain vigilant, as well as repressive efforts in the form of application of the law. 3. Judging from the Jinayah law, hypnosis is a crime that is difficult to prove (Al-bayyinah) because of the lack of guidance (Qarinah) and witnesses (Shahadah), except for the recognition (Iqrār) from the victim and the perpetrator. Fraud can be classified as a punishment imposed by Jarimah ta'zir because it is based on fraud that does not fall into the category of Jarimah hudud or Qisas whose amount has been determined.